DEVELOPING MEDIA OF MATHEMATICS LEARNING BASED PROBLEM BASED LEARNING TO LEARN LINE AND ANGLE FOR 7TH JUNIOR HIGH SCHOOL - Rofiah Yusuf; Murdanu . (Jurnal Pedagogi Matematika, 2017)
This research was about development research that had purpose to make product and describethe quality of product that must fulfill aspect of validity, practicality, and effectiveness. The productconsisted of student worksheet and visual aid (frame of line and angel) based on Problem BasedLearning approach to learn mathematics material about line and angle especially in basic competence3.13 and 4.13 for 7th grade of junior high school.This development research used Plomp methods with 5 phases such as phase of preliminaryinvestigation, phase of design, phase of realization or construction, phase of test, evaluation, andrevision, and phase of implementation. Subject of this research was 32 students of 7th grade of juniorhigh school 1 Mlati with 90,62% of students passed school grade value, it meaned learning objectiveswere achieved.The result of this development research were: (1) product was valid to help students learnabout line and angle, basic competence 3.13 and 4.13; (2) product was practise to help teacher andstudents in learning process; (3) product was effective with achieved of learning objectives. Thisproduct was valid, practice, and effective so it could be implemented in learning process.Key words: line and angle, worksheet and visual aid (frame of line and angle), Problem BasedLearning, Plomp methods.